'A passion for justice': Martin Luther King, Jr. and G. W. F. Hegel on 'world-historical individuals'. (February 2017) - Vernon, Jim
In this article, I explicate Martin Luther King, Jr.'s account of emancipatory history and activism by examining the influence of G. W. F. Hegel's account of world-historical individuals on his thought. Both thinkers, I argue, affirm that history's spiritual destiny works through individuals who are driven by the contingencies of their subjective character and given situation to undertake particular actions, and yet who nevertheless freely and decisively break the new from the old by forsaking subjective satisfaction to spur events forward to a more rational state of affairs. This synthetic unity of abstract freedom and concrete embodiment reflects the 'civil war' between the universal and infinite essence, and particular and finite passions, that King and Hegel identify as equally constitutive of human will. Through an examination of King's account of Rosa Parks' pivotal arrest, I develop the consequences of this 'Hegelian' view for our understanding of political action and historical progress.